Preliminary observations on the San Martin titi monkey Plecturocebus oenanthe Thomas, 1924 (Mammalia: Primates: Pitheciidae) vocalizations at Tarangue, Peru - Aldrich, Brooke Catherine; Shanee, Sam (Neotropical Primates, 2016)
No abstract